Effective Learning of Foreign Languages with the Help of Information Technologies - Jorayeva Yulduz Rozikulovna (Scientific Trends, 2023)
This article provides detailed information about improving foreign language among young people, guiding the young generation to foreign languages and effectively learning foreign languages with the help of information technologies.
Keywords: Media; technologies; information communications; modern methods.